The direct inverse method: A novel approach to estimate adsorption isotherm parameters - Cornel, Jeroen; Tarafder, Abhijit; Katsuo, Shigeharu; Mazzotti, Marco (Journal of Chromatography A, 2010)
A novel method to estimate adsorption isotherm parameters is presented and its applicability is studied through synthetic as well as experimental data. This approach assumes a linear dependency of the UV absorption intensity on the solute concentration in the fluid phase, at least in certain ranges of the UV spectra. It was demonstrated that by fitting the absorption profiles, i.e. the new direct inverse method, and by fitting the concentration profiles, i.e. the classical inverse method, very similar adsorption isotherm parameters can be obtained. The findings presented in this work have as important implication the elimination of the requirement of converting a measured absorption intensity into a concentration value, i.e. the elimination of the calibration of the UV signal.